Merdeka Curriculum Based EBA Learning Model in Elementary Schools - Miftahul Husni; Al Ihwanah Al Ihwanah; Djoko Rohadi Wibowo; Maulana Arafat Lubis (UIN Siber Syekh Nurjati Cirebon, 2023)
Abstract Merdeka Curriculum is the main gate to developing the potential of elementary school-level students to learn independently through teacher guidance. Currently, the government of the Republic of Indonesia hopes that the Program for International Student Assessment (PISA) results from data in 2018 can be improved. The research objective was to improve the learning outcomes of Pancasila and Civic Education in the aspects of spiritual attitudes, social attitudes, knowledge, and skills of students by applying the EBA learning model to the subject matter of ethnic, social, and cultural diversity in Indonesia. The research subjects were 24 students of class IV of a public elementary school in Padangsidimpuan City, Indonesia. This research used the Kemmis & McTaggart class action research method, which involved planning, acting, observing, and reflecting. Data were collected by using tests, observations, and interviews. The data were analyzed descriptively with qualitative and quantitative approaches. The study's results prove that after applying the EBA learning model, studentsâ€™ learning outcomes have increased from pre-test, post-test I, and II to post-test III with an average score of 86.71 and a completeness percentage of 87.5%.Keywords: curriculum merdeka, EBA learning model, elementary school.Â Â AbstrakKurikulum Merdeka merupakan gerbang utama untuk mengembangkan potensi siswa jenjang sekolah dasar agar mampu belajar mandiri melalui bimbingan guru. Saat ini, pemerintah Republik Indonesia berharap agar hasil Program for International Student Assessment (PISA) dari data tahun 2018 dapat ditingkatkan. Tujuan penelitian adalah untuk meningkatkan hasil belajar PKn pada aspek sikap spiritual, sikap sosial, pengetahuan dan keterampilan siswa dengan menerapkan model pembelajaran EBA pada mata pelajaran keberagaman suku, sosial dan budaya di Indonesia. Subyek penelitian adalah 24 siswa kelas IV di sebuah sekolah dasar negeri di Kota Padangsidimpuan, Indonesia. Penelitian ini menggunakan metode penelitian tindakan kelas Kemmis & McTaggart yang meliputi perencanaan, tindakan, observasi, dan refleksi. Pengumpulan data menggunakan tes, observasi, dan wawancara. Data dianalisis secara deskriptif dengan pendekatan kualitatif dan kuantitatif. Hasil penelitian membuktikan bahwa setelah diterapkan model pembelajaran EBA, hasil belajar siswa mengalami peningkatan dari pretes, postes I, dan II menjadi postes III dengan skor rata-rata 86,71 dan persentase ketuntasan 87,5. %.Kata kunci: kurikulum merdeka, model pembelajaran EBA, sekolah dasar